The influence of priming on reference states - Astrid Matthey (Games, 2010)
Experimental and empirical evidence shows that the utility an individual derives from a certain state depends on the reference state she compares it to. According to economic theory, the reference state is determined by past, present and future outcomes of either the individual herself or her reference group. The experiment described in this paper suggests that, in addition, reference states depend to a significant degree on environmental factors not relevant for outcomes. It indicates that reference states - and hence utility - can relatively easily be influenced without changing people's outcomes, e.g., through priming.
Keywords: 330; reference state; utility; prospect theory; manipulation; priming; experiment